Cell phone at your workplaces - Ismail, Fadillah; Abu Bakar, Nor Aiza Aliah; Ali Hassan Humaid Alhosani, Adnan; Salleh, Siti Hasliah (Penerbit UTHM, 2020)
Digital technology has become an integral part of people life because of it always ask the people to gain a new information search and learn the new things such as they can communicate very well with another people at organization. The benefit of digital technology is there are most frequently used electronics tool among young people and workers (Colbert, Yee & George, 2016). They have good competency character in course among them and give positive feedback with technology by worker distribution. Then, it will give the company positive impact because of their skill and be comfort easier to achieve more of using technology. Then, it will help and give benefit to organizations because they can work well.